Service Limit Criteria for Deflection and Cracking in Partially Prestressed Beams - Alam, Khondaker Shamsul (1985)

(untitled)
This thesis has been concerned with the primary objective of studying the serviceability behavior of partially prestressed concrete beams. Seven simply supported rectangular beams were tested on an effective span of 2.745 m subjected to two third point loadings. The variables were the amount of prestressing wires and ordinary reinforcement steel. The effect of bond was also investigated. Four beams were fully bonded by using pressurised grouting while three other beams were tested unbonded. Crack widths and deflections were recorded at various loadings, and crack propagations observed. The results obtained were compared with theoretical values proposed by various authors. Results were also compared with the service limit criteria for cracking and deflection according to the British Standards code of practice, CP 110:1972. It was observed that the service limit criteria for cracking and deflection as set out by the code are too conservative for rectangular beams tested. It was found that the existing theory greatly underestimates the ultimate as well as service load carrying capacity and overestimates crack widths of partially prestressed concrete beams. It was also found that the nature of bonding has a great influence on crack widths and deflections. Bonded beams greatly improve on serviceability by having increased load carrying capacity and reduced crack width.